2020
DOI: 10.3389/fphys.2020.00740
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Physical Exercise on the Quality of Life, Exercise Ability, and Cardiopulmonary Fitness of Patients With Atrial Fibrillation: A Systematic Review and Meta-Analysis

Abstract: Objective: Physical exercise is recommended to help prevent lifestyle diseases. The present study was designed to quantify the efficacy of physical exercise on the quality of life (QoL), exercise ability and cardiopulmonary fitness of patients with atrial fibrillation (AF). Method: A comprehensive systematic literature search was performed in Medline, Embase, Cochrane Library, Web of Science and PubMed databases (from 1970 to December 1st, 2019) for randomized controlled tria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 60 publications
2
12
1
Order By: Relevance
“…While one carried out the evaluation in the 1st, 4th, 6th month [18] after the intervention, the other [16] applied the SF-36 questionnaire adapted for his study only once [34], which may have interfered in the QoL analysis. Therefore, as in other studies, positive effects of CR were observed on QOL, exercise capacity and cardiopulmonary fitness in individuals with AF, highlighting the findings of this review [35].…”
Section: Discussionsupporting
confidence: 83%
“…While one carried out the evaluation in the 1st, 4th, 6th month [18] after the intervention, the other [16] applied the SF-36 questionnaire adapted for his study only once [34], which may have interfered in the QoL analysis. Therefore, as in other studies, positive effects of CR were observed on QOL, exercise capacity and cardiopulmonary fitness in individuals with AF, highlighting the findings of this review [35].…”
Section: Discussionsupporting
confidence: 83%
“…Both groups fared similarly despite the 336-minute difference in total exercise conditioning volume (CR: 720 minutes vs HIIT: 384 minutes). A recent meta-regression analysis in patients with AF reported that exercise sessions of at least 60 minutes could significantly increase 6MWT distance, yet the patients in the HIIT group of our study demonstrated significant increases after a program duration of only 23 minutes. A meta-analysis showed, however, superior increases of 47 m in 6MWT distance following MICT-based CR compared with control (ie, usual care) in patients with paroxysmal, persistent, and permanent AF .…”
Section: Discussioncontrasting
confidence: 78%
“…During our search, similar exercise-related systematic reviews on patients with AF were identified 33–36 . The first systematic review 33 investigated the benefits of physical activity in AF patients with 1056 participants from 36 articles.…”
Section: Discussionmentioning
confidence: 99%
“…The most recent systematic review and meta-analysis (12 studies, n = 819 participants) 36 also reported a significant improvement in vitality [SMD: 0.51 (95% CI: 0.31–0.71)], physical functioning [SMD: 0.63 (95% CI: 0.18–1.09)] and general health [SMD: 0.64 (95% CI: 0.35–0.93)], although the heterogeneity was high in the last two domains ( I 2 = 85.6%, and I 2 = 66.2% respectively). V̇O 2peak and 6MWT were also significantly improved [SMD: 0.37 (95% CI: 0.16–0.57), SMD: 0.69 (95% CI: 0.19–1.19) respectively] but heterogeneity was high in the 6MWT ( I 2 = 70.6%) owing to the training duration.…”
Section: Discussionmentioning
confidence: 99%